A study of the relationship between seed quality and commercial sprouting quality of green gram (Vigna mungo L. Hepper) and black gram (Vigna radiata L. Wilczek) : a thesis presented in partial fulfilment of the requirement for the degree of Master of Applied Science in Seed Technology at Massey University, Palmerston North, New Zealand - DeFilippi, Joanne Maree (Massey University, 1998)
Standard seed quality tests (seed moisture content, thousand seed weight, topographical tetrazolium, germination and seedling evaluation); vigour tests (accelerated ageing, conductivity, rate of germination and uniformity of germination) and industry based tests (oversoaks and sprouters) were evaluated for their ability to rank eight black gram (Vigna mungo L. Hepper) seed lots and seven green gram (Vigna radiata L. Wilczek) seed lots for the purpose of commercial sprouting. Each seed lot was sprouted using simulated commercial conditions (19°C water temperature; 20°C cabin temperature; dark; 5 days). Seed lots which performed well under these small scale commercial production (SSCP) conditions, in terms of total fresh yield and healthy sprout yield, were considered to be the best quality seed lots. All tests were able to significantly determine differences among seed lots within each species. Linear regression analysis indicated that interim germination (R² = 79.1%), final germination (R² = 76.3%), seed moisture content (SMC) (R² = 63.7%) and oversoak sprouters (R² = 60.6%) were significantly related to total fresh yield in green gram seed lots only. No other significant linear relationships were found for either green gram or black gram. Incorporating interim germination, final germination, SMC and oversoak sprouters in a multivariate analysis reduced the level of unexplained variation in green gram total sprout yield. The best combination was interim germination and oversoak sprouters (R² = 84.2%); Y = 9.1(%interim germination) - 8.1 (oversoak %sprouters) + 731.4. Very similar to this was the combination of final germination and SMC (R² = 83.8%); Y = 4.7(%final germination) + 15.3(%SMC) + 165.4. The reason for the differing responses of black gram and green gram was not explained, but both genetic variation and differences in environment during seed development and handling prior to testing are likely causes. It was not possible to use any individual or combination of tests to predict sprouting performance for green or black gram with the accuracy the sprouting industry would require. However, the results have shown that it will be possible to eliminate many of the seed quality tests examined from further research. Refinement of test procedures for the relevant standard and industry based tests will be required to provide the accurate seed testing regime needed by the sprouting industry.
Page 68 is missing from the original copy.
Keywords: Mung bean; Seeds; Quality; Viability